Kiat Penelitian Dengan Model Pendekatan Telaah Kepustakaan - Guntur Putra Jaya; Idi Warsah; Muhammad Istan (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Each study has different characteristics, so the stages and processes involved in conducting library research may vary depending on the objectives and research problems. So this paper aims to provide an overview as a basic guideline that can be used in conducting library research in the field of education in conducting further research. Library research is a research method that uses sources found in libraries, such as books, journals, articles, and other documents, to collect data and information needed in a study. This literature research is usually done as a first step in research and can be used to determine the background, understand the context, and find ideas for further research. The main strategies and components in using literature research with tips that can help in carrying out effective and efficient literature research are First, clearly identify the problem and research objectives. Second, search for relevant and trusted resources such as books, journals, articles, etc. Third, Analysis, evaluation, and selection of found resources to determine their validity and feasibility, Fourth, Organization and records of research results to facilitate the integration of information and Fifth, Integration of research results and preparation of systematic and logical reports.